Spiritual experience in digital interaction based on Insan-Centered Design/ Fadzlin Ahmadon ... [et al.] - Ahmadon, Fadzlin; Mahmud, Murni; Saidin, Aznan Zuhid; Azuddin, Muna (Faculty of Information Management, 2025)
This concept paper introduces Insan-Centered Design, a design approach that integrates Islamic ethics and values with human-centered design principles. It uniquely addresses both the physical and spiritual needs of users, reflecting the Islamic view of life as a temporary state with a focus on achieving peace in the afterlife. Central to Insan-Centered Design is the promotion of ihsan (excellence), and the adherence to Maqasid al-Shariah(objectives of Islamic law). The approach is further enriched by incorporating taqwa (God-consciousness), khalifah(stewardship) and the principle of amar ma'ruf nahi mungkar (enjoining good and forbidding evil) into digital interactions. This paper presents practical applications of Insan-Centered Design through scenarios such as mindful financial apps, Islamic navigation systems, and ethical online platforms, demonstrating how technology can align with Islamic values and ethical considerations. Insan-Centered Design thus emerges as a transformative approach, offering a fresh perspective in technology design by integrating Islamic values into technology and considering the lasting impact of our digital interactions.